Collaboration In the Medical Device Innovation During the Covid-19 Pandemic in Indonesia: A Network Analysis - Purwaningsih, Indah; Hardyati, Ria (Unit Research and Knowledge, School of Business and Management, Institut Teknologi Bandung, 2024)
Abstract. This study identifies social network of medical device innovation during the Covid-19 pandemic in Indonesia. We employed the Social Network Analysis (SNA) from the collected data through semi-structured interview and document analysis. We focused on two case studies of therapeutic devices that have successfully been collaboratively developed and gained marketing license for Covid-19 treatment in Indonesia, i.e. Gerlip HFNC-01 and Covent-20. The study finds that heterogenous actors (university, public research institute, firm, government, society, non-government organization, users) share resources in each stage of the innovation process that demands distinct functions and resources from idea generation, product development, testing and implementation. The relations between actors happen by some means: joint project, resource sharing, and government direction. Key actors should be able to reach as many actors and bridge communication in order to develop network interdependence and to facilitate innovation. Eventually, the government plays a significant role to accelerate innovation through some fruitful policy packages. Keywords: Collaboration, innovation process, medical device, social network analysis